Other well-defined immunodeficiency syndromes - (:unkn) unknown (Springer Berlin Heidelberg, 2012)
Five broad and major groups of PID classification have been known as CID, PAD, phagocyte disorders, complement deficiencies, as well as other well-defined immunodeficiency syndromes. The former includes Wiskott-Aldrich syndrome (WAS), which presents as a clinical triad of eczema, thrombocytopenia, and recurrent infections. Patients exhibit a variety of laboratory abnormalities, including decreases in peripheral blood CD8+ T cells. A flow cytometric assay for the detection of Wiskott-Aldrich syndrome protein (WASP) protein in lymphocytes has recently been described and applied to the diagnostic evaluation of both WAS patients and carriers of WASP mutations [1]. © Springer-Verlag Berlin Heidelberg 2012.